Accuracy of indirect bonding trays - a measurement algorithm - Koch, Petra Julia; Albrecht, Marco; Lin, Wei-Cheng; Jost-Brinkmann, Paul-Georg (International journal of computerized dentistry, 2022)
To present an image-processing measurement algorithm to evaluate the transfer accuracy of indirect bonding (IDB) trays, exemplified by a CAD/CAD-based IDB tray integrated into a digital orthodontic workflow. Plaster models of 24 patients with full dentition and different malocclusions were scanned with an intraoral scanner (TRIOS®, 3Shape, Copenhagen, Denmark) to receive digital models, which served for the virtual placement of orthodontic brackets in a simulation software (OnyxCeph³™, Image Instruments, Chemnitz, Germany). The resulting STL-files were sent to CA Digital for production of INDIVIDUA® IDB trays (CA Digital, Hilden, Germany). Upon receipt, the brackets were transferred to the respective plaster models using these trays. Finally, a second scan was performed to record the actual bracket position. The transfer accuracy was then analysed by a measurement algorithm scripted to automation, which calculated the deviations of the planned and the real bracket positions with a local best-fit alignment resulting in three linear and three angular measurements for each bracket. In total, 622 brackets and tubes were transferred successfully. The presented algorithm analysed the transfer accuracy and demonstrated that the linear measurements were in 98.3% within the range of the American Board of Orthodontics standard. The angular measurements were in 86.7% within this range when using the INDIVIDUA® IDB tray. Scripted measurement algorithms facilitate the evaluation of present and future materials and designs for IDB trays to find an efficient solution for the orthodontic practice. The INDIVIDUA® IDB tray is a digital alternative to conventional indirect bonding trays.